The Campus Canopy,1935-02-06 - Georgia State Womans College (Valdosta State University Archives and Special Collections, 1935)
Reverend Eyler is Assembly Speaker; Dr. Beebe Thrills Audience Sunday with Accounts of Deep Sea Dives; S.G.A. Hears Talk on Character; Y.W.C.A. Sponsors Alumna Speaker; Check-up Shows Journal Favorite; Vesper Programs;
Georgia State Womans College. "The Campus Canopy, February 6, 1935." Vol.01, No.08. Valdosta State University Archives and Special Collections, 2018. http://hdl.handle.net/10428/2978. ### Persons Mentioned ### Alys Dawn Cullens; Annie Laura Rentz; Armand Eyler; Arthur Parramore; Barbara Hatcher; Baron Von Neurath; Bill Thomas; Bobby Cochran; Bud Holt; C. J. Morris; C. J. Nix; Camille Rogers; Carolyn Cook; Carolyn Whipple; Daisy Daniels; Dan Dunn; Daniel Ashley; D. S. Boucher; Doris Swindle; Dorothy Ogletree; J.A. Durrenberger; Edith Bennett; Albert Einstein; Elizabeth Macon; Elizabeth Wilkes; Estelle Roberts; Ethelyn Massey; Eugene Ormandy; Evelyn May; Reverend Eyler; Flash Gordon; Frances Dekle; Francis Hinson; Francis Whitaker; Garfield; Geraldine Collins; Gertrude Gilmer; Helen Vinson; Henry Kate Gardner; Hitler; Homer Eberhardt; Howard Bridges; Hubert Baker; J. H. Morgan; J. P. Morgan; Jack Woodford; James A. Garfield; Jerry Hatcher; Jerry Rivers; Jesse Morgan; Kathryn McHale; Kitsie Smith; L. L. Lundy; L. Smith; Lawton Ursrey; Leila Urquhart; Lena J. Hawks; Leonora Dufour; Lillian Slocumb; Louise Hardy; Louise Smith; Lucille Tyson; M. W. Davis; Madee Watson; Marie Joiner; Marie Middleton; Marjorie Jordan; Marjory Jordon; Marvin Register; Mary Elizabeth Nix; Mary Elizabeth Weatherford; Mary Lois Hitch; Matilda Tillman; Meta Glass; Nancy Carroll; Patsy Sparks; Paula Sapp; Pearl Wilson; Rachel Coxwell; Frank Reade; Ruth Loughridge; Ruth Williams; Ruth Wood; Sallie Prescott; Sally Morris; Sara Martha Pyle; Sue Patterson; Thera Hambrick; Thomas Lawrence; Tommy Brown; Tredeva Ogletree; Verdell Dickerson; Virginia Anne Groover; Virginia Dismuke; W. B. Watkins; W. G. Eager; Walter Frazier; Warner Baxter; William Beebe; Winnie Davis; Wynelle Vincent; Buddy Rogers; Warner Baxter; ### Locations Mentioned ### Adel, Georgia; Baxley, Georgia; Camilla, Georgia; Fitzgerald, Georgia; Jasper, Georgia; Albany, Georgia; Austria; Bermuda; Boston, Massachusetts; Chicago< Illinois; Doerun, Georgia; France; Geneva Institute; Georgia; Germany; Halcyondale, Georgia; Hazlehurst, Georgia; Hitlerland; Homerville, Georgia; Jacksonville, Florida; Mars; Moultrie, Georgia; Mystic, Georgia; New York, New York; Quitman, Georgia; West Hall Rotunda (Valdosta State University); Saar Basin; Tifton, Georgia; Uruguay; United States; Valdosta, Georgia; Vienna, Austria; Virginia; Wall Street; Washington; ### Organizations Mentioned ### Minneapolis Symphony; American Association of University Women (A. A. U. W.); Allied Powers; American Association of Uni; Andrew College; Atlanta Journal; Atlantic Monthly; College of Arts and Sciences; Emory University; Episcopal Church; F. E. R. A.; Florida State College for Women; Gene Talmadge; League of Nations; Library Committee; Literary Digest; Macon Telegraph; Mills College; National; The Times; University of Chicago; Vesper Programs; Waycross Journal;
Keywords: Newspapers; Georgia State Womans College -- Students -- Periodicals; College student newspapers and periodicals -- Georgia -- Valdosta